Livelihoods, Value and Knowledge in Contemporary Paraguay - Finnis, Elizabeth; Millman, Heather (Anthropologica, 2015)
In this article we explore the connections among value, knowledge and livelihoods in contemporary Paraguay. Although the specifics of their livelihood activities differ, the experiences of traditional medicinal plant herbalists (yuyeros) in Asuncion and rural campesino farmers thematically overlap. Both participant groups argue that their cultural and practical knowledge is important to the nation, but that their contributions—both actual and potential—to Paraguayan life and the nation are restricted by policies and practices that ignore and exclude them. Our analysis of the ways yuyeros and campesinos think about their livelihood activities demonstrates different valuations of certain kinds of knowledge and the implications this has for attempts to make a living.